2022
DOI: 10.3102/00346543221123816
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Morphological Awareness with Language and Literacy Skills Vary Depending on Orthographic Depth and Nature of Morphological Awareness

Abstract: We examined the relation of morphological awareness with language and literacy skills, namely phonological awareness, orthographic awareness, vocabulary, word reading, spelling, text reading fluency, and reading comprehension. We also examined potential moderators of the relations (grade level, orthographic depth of language, receptive vs. productive morphological awareness, inflectional vs. derivational vs. compound morphological awareness, and L1/L2 status). After systematic search, a total of 232 articles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 82 publications
(174 reference statements)
0
30
2
Order By: Relevance
“…Morphological awareness (MA) is a type of metalinguistic awareness often defined as the ability to manipulate morphemes (the smallest unit of meaning) and reflect on morphological structures of words (Carlisle, 2003;Kuo & Anderson, 2006;Levesque et al, 2021;Nagy et al, 2014). MA has been identified as a significant correlate and predictor, often independent of PA, of various reading-related abilities, including word reading (fluency), vocabulary knowledge, and reading comprehension, in hearing students of diverse backgrounds (Ke et al, 2021;Lee et al, 2022;Ruan et al, 2018). In the literature on DHH students, other than a few narrative reviews (e.g., Cannon & Trussell, 2021;Gaustad, 2000;Nielsen et al, 2011), there has been little effort to systematically review studies on MA and reading (see, however, Trussell & Easterbrooks, 2017), not to mention any meta-analysis on their correlations.…”
Section: Morphological Awareness and Dhh Students' Reading-related Ab...mentioning
confidence: 99%
See 4 more Smart Citations
“…Morphological awareness (MA) is a type of metalinguistic awareness often defined as the ability to manipulate morphemes (the smallest unit of meaning) and reflect on morphological structures of words (Carlisle, 2003;Kuo & Anderson, 2006;Levesque et al, 2021;Nagy et al, 2014). MA has been identified as a significant correlate and predictor, often independent of PA, of various reading-related abilities, including word reading (fluency), vocabulary knowledge, and reading comprehension, in hearing students of diverse backgrounds (Ke et al, 2021;Lee et al, 2022;Ruan et al, 2018). In the literature on DHH students, other than a few narrative reviews (e.g., Cannon & Trussell, 2021;Gaustad, 2000;Nielsen et al, 2011), there has been little effort to systematically review studies on MA and reading (see, however, Trussell & Easterbrooks, 2017), not to mention any meta-analysis on their correlations.…”
Section: Morphological Awareness and Dhh Students' Reading-related Ab...mentioning
confidence: 99%
“…Developmentally, the importance of MA, and its relative importance with that of PA, is also in line with stage/phase models of reading acquisition where English-speaking children at a relative late stage (e.g., the consolidated alphabetic phase in Ehri, 2005) employ chunking (e.g., syllables and morphemes) to read multisyllabic/multimorphemic words. Numerous studies have found MA as a significant predictor, over and above phonological skills, of both word reading accuracy and fluency across languages and reader groups (see the meta-analytic findings reported in Ke et al, 2021Ke et al, , 2023Lee et al, 2022;Ruan et al, 2018).…”
Section: Morphological Awareness and Reading Developmentmentioning
confidence: 99%
See 3 more Smart Citations